Resurrecting the nepeš - Wright, Jim (2021)
Our culture’s approach to dementia typically focuses on preserving the person as they once were. Mental exercises, special diets, and entire memory care facilities are designed to maintain the “previous person.” As important as this is to family and friends, it can be challenging and burdensome to the person who is living with dementia, a person who may not recall, or want to recall, their past life. This essay asserts that the emphasis on maintaining the previous person (and the resultant de-emphasis on honoring the new person) often results from a belief in our innate permanence, particularly the belief in our immortal, immutable soul. Because of this insistence on innate immortality, we tend to undervalue those who fail to live up to the expectations of permanence. The author calls for a renewed emphasis on nepeš, ancient Israel’s concept of the mortal, fleeting human life. By acknowledging our impermanence, we may be able to better identify with and value those who live with dementia and design environments that honor and enable people who are becoming someone new.
Keywords: Nepeš; Alzheimer’s Disease; Dualism; Immortality; Frailty; Dementia